2017
DOI: 10.1002/jsfa.8505
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, molecular and ultrastructural analyses during ripening and over‐ripening of banana (Musa spp., AAA group, Cavendish sub‐group) fruit suggest characteristics of programmed cell death

Abstract: This study shows for the first time that ripening and over-ripening of banana peel share physiological and molecular processes previously described in plant PCD. SRDS could represent a morphotype of PCD that characterizes a structural and biochemical failure in the upper layers of the peel, thereafter spreading to lower and adjacent layers of cells. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Ramírez‐Sanchez et al . showed that protease activity evaluated at pH 5 increased over time in whole peel tissue during ripening and overripening.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ramírez‐Sanchez et al . showed that protease activity evaluated at pH 5 increased over time in whole peel tissue during ripening and overripening.…”
Section: Discussionmentioning
confidence: 99%
“…Ramírez-Sanchez et al 22 showed that protease activity evaluated at pH 5 increased over time in whole peel tissue during ripening and overripening. Preliminary studies on banana peel wileyonlinelibrary.com/jsfa In-gel nuclease activity assay of outer 1 mm of peel tissue during ripening and overripening of banana fruit following exposure to 20 ∘ C and 80-85% RH or 5 ∘ C and 80-85% RH for 4 days followed by storage at 20 ∘ C. Protein (1 μg) was resolved using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) in 120 g L −1 polyacrylamide gels containing 30 μg mL −1 heat-denatured herring sperm DNA as in-gel substrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations